Maximal aerobic power in triathletes during swimming, cycling, and running - Kerr, C. G.; Trappe, T. A.; Trappe, S. W. (Medicine & Science in Sports & Exercise, 1996)
It was found that the VO2max values in each of the triathlon activities were different despite being well conditioned in all three. Implication. It is erroneous to assume that absolute VO2max measures in one activity will be similar in another.